Inteligência artificial: produção científica da enfermagem brasileira: Artificial Intelligence: scientific production of Brazilian nursing (Revista Científica Integrada, 2024)
Objective: Identify and describe national publications on Artificial Intelligence (AI) and Nursing. Methods: An Integrative Literature Review was carried out in the Virtual Health Library (VHL), with the DeCS “Artificial Intelligence” and “Nursing” and in the Generative Pre-Trained Transformer (ChatGPT), for the guiding question: “What has been scientifically produced by Brazilian nursing on AI?”. The results pointed to four scientific articles in the VHL and a list of possibilities in ChatGPT. Results: Studies were identified on the challenges and opportunities of AI, the analysis of student emotions by AI, an AI algorithm for sepsis detection and a prototype for Nursing Diagnoses with AI. Conclusion: It is evident that Nursing has an open and very promising field for using AI in favor of care based on scientific evidence and nursing courses, through their program contents, must include the theme of AI in a creative way to awaken in its students the vision of the future in health care in a critical and reflective way.
Keywords: Nursing; Artificial intelligence; Technology